2021
DOI: 10.1177/03010066211042186
|View full text |Cite
|
Sign up to set email alerts
|

What is the Link Between Mental Imagery and Sensory Sensitivity? Insights from Aphantasia

Abstract: People with aphantasia have impoverished visual imagery so struggle to form mental pictures in the mind's eye. By testing people with and without aphantasia, we investigate the relationship between sensory imagery and sensory sensitivity (i.e., hyper- or hypo-reactivity to incoming signals through the sense organs). In Experiment 1 we first show that people with aphantasia report impaired imagery across multiple domains (e.g., olfactory, gustatory etc.) rather than simply vision. Importantly, we also show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 101 publications
6
44
0
Order By: Relevance
“…The main limitation of our study is that the sample is not large enough for comparisons across subgroups, or for investigation of the risk behavior of individuals with aphantasia (those with no mind’s eye) or with hyperphantasia (whose mental images are as vivid as actual visual perception). While aphantasia has been associated with impaired imagery across multiple sensory domains (including auditory, olfactory and gustatory imagination) 35 , 36 , and with intellectual disability 37 , we are not aware of a study that relates it to choice behavior. Such an investigation would require a more targeted participant recruitment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is that the sample is not large enough for comparisons across subgroups, or for investigation of the risk behavior of individuals with aphantasia (those with no mind’s eye) or with hyperphantasia (whose mental images are as vivid as actual visual perception). While aphantasia has been associated with impaired imagery across multiple sensory domains (including auditory, olfactory and gustatory imagination) 35 , 36 , and with intellectual disability 37 , we are not aware of a study that relates it to choice behavior. Such an investigation would require a more targeted participant recruitment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Zeman et al (2015) noted that ten out of 21 participants reported that imagery in all sensory modalities was affected. Subsequent work indicates that a majority of those lacking visual imagery also lack imagery in other sense modalities (Dance et al, 2021;Dawes et al, 2020;Zeman et al, 2020).…”
Section: Abstract (Optional)mentioning
confidence: 99%
“…Second, the term 'dysikonesia' (Dance et al, 2021) has been suggested for multisensory or global aphantasia, on the mistaken assumption that aphantasia refers only to the lack of specifically visual imagery. Dance et al (2021) justify the assumed specificity of aphantasia for visual imagery by referring to the same Greek word phantázo.…”
Section: Abstract (Optional)mentioning
confidence: 99%
See 2 more Smart Citations